Pengaruh Disiplin Kerja Dan Komunikasi Terhadap Kinerja Karyawan di PT. Sarana OTW Indonesia - Alya Raisyadini Salsabila; Susiana Dewi Ratih; Hasan Basri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Human resources are a crucial factor in determining the success or failure of an organization. Organizations continually strive to acquire resources that can ease the burden of achieving their goals. This study employed a quantitative, descriptive design, collecting primary data by distributing questionnaires to respondents, namely employees at PT. Sarana OTW Indonesia, using a sampling method. The results of the study include work discipline as an independent variable X1 having a significant influence on employee performance with a calculated t value> t table of 5.715> 2.008 with a significance of 0.000 <0.05. In addition, variable X2, namely Communication, has a significant influence on employee performance with a calculated t value> t table of 3.493> 2.008 with a significance value of 0.000 <0.05. Then, together, work discipline and communication have an effect on employee performance with a calculated F value> F Table of 38.928> 1.659 with a significance of 0.000 <0.05. The conclusion of this study is that work discipline and communication influence employee performance at PT. Sarana OTW Indonesia. The R value of 0.747 or 74.7% means the relationship between work discipline and communication on employee performance. The R Square value of 0.694 or 69.4% of work discipline and communication is able to influence employee performance, while the remaining 30.6% is influenced by other variables.